The Technique Triad Theory - Williams, Brogan; Horschig, Aaron (British Journal of Healthcare and Medical Research, 2023)
A common theme that has been recently perpetuated through the medical community is the oversimplification of injury science to the equation of load versus capacity and the disregard for the influence of movement quality. The Adaptation Model is based on the belief that one can recover and/or adapt to any stimulus or stress that is gradually applied as long as it does not breach the system’s capacity; and that, as humans, we can infinitely become better suited to our environment regardless of what this environment may entail. Many who support this hypothesis reject the importance of biomechanics, technique, and movement proficiency in regard to injury prevention and rather promote this idea of adaptation in isolation. Building capacity through many repetitions gradually involves neurophysiological adaptations that improve skill acquisition, neuromuscular efficiency, and technique. Therefore the “adaptation model” inherently involves an element of “technique” in itself. “Load” and “Capacity” play a key role in one’s ability to adapt, grow and perform at their best. However, this duality is incomplete without the 3rd pillar - technique. In order to maintain ideal movement proficiency and drive physiological adaptations, we must increase the load within the context of what our skill and technique will allow. Although technique quality is described often on a sliding spectrum-like scale, as requiring sufficient competency within certain fundamentals as a prerequisite to increasing load allows you to improve skill without increasing the risk of breaching your tissue tolerances. Increase load too quickly, and you risk sporadic and uncontrolled migration of forces onto parts of your body or tissue systems that do not yet have the required capacity to handle such stress. With the proper movement patterns ingrained and the appropriate dosage or load progressively challenging the capacity, the programming now reflects the intensity of such stimuli based on the athlete’s ability to recover from the fatigue debt created in training. As the programming progresses and the load is increased, capacity requires technique and the ability to move proficiently through the sport-specific movement. 1) Technique permits load because load requires technique, 2) Load challenges capacity because capacity dictates load and 3) Capacity requires technique because technique protects and maximizes capacity.